2019
DOI: 10.3390/coatings9060387
|View full text |Cite
|
Sign up to set email alerts
|

Modifying Plasmonic-Field Enhancement and Resonance Characteristics of Spherical Nanoparticles on Metallic Film: Effects of Faceting Spherical Nanoparticle Morphology

Abstract: A three-dimensional finite-difference time-domain study of the plasmonic structure of nanoparticles on metallic film (NPOM) is presented in this work. An introduction to nanoparticle (NP) faceting in the NPOM structure produced a variety of complex transverse cavity modes, which were labeled S11 to S13. We observed that the dominant S11 mode resonance could be tuned to the desired wavelength within a broadband range of ~800 nm, with a maximum resonance up to ~1.42 µm, as a function of NP facet width. Despite b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 60 publications
0
20
0
Order By: Relevance
“…To visualize how the QNMs evolve with varying facet width w, Fig. 3(d To further explore the radiative nature of each QNM, we estimate the radiation efficiency of the ( m) mode as Figure 4 shows the radiation efficiencies of (10), (20), (30), (40), (11), (21), (31), (41), (22) and (33) modes. Overall, the ( 0) modes are the dominant radiative channels of NPoMs, as one would expect.…”
Section: Faceted Nanocavitiesmentioning
confidence: 99%
See 2 more Smart Citations
“…To visualize how the QNMs evolve with varying facet width w, Fig. 3(d To further explore the radiative nature of each QNM, we estimate the radiation efficiency of the ( m) mode as Figure 4 shows the radiation efficiencies of (10), (20), (30), (40), (11), (21), (31), (41), (22) and (33) modes. Overall, the ( 0) modes are the dominant radiative channels of NPoMs, as one would expect.…”
Section: Faceted Nanocavitiesmentioning
confidence: 99%
“…1(d, e) and 2(f-j) for the w = 20 nm NPoM. Nonetheless, the symmetries of these QNMs are preserved for all facet widths, validating the nomenclature used in this article.Previous studies where the far-field spectra of NPoMs were analysed[17][18][19]21 have identified only the ( 0) and ( 1) modes. The ( 0) modes are bright and can be efficiently excited by the vertical (z-axis) component of an exciting plane wave.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The refractive index of gold was taken from the Johnson and Christy database and was modeled using Lorentz-Drude dispersion fitting. [44][45][46][47][48] e w ð Þ ¼ 1…”
Section: Modelingmentioning
confidence: 99%
“…These systems display rich plasmonic modes and have a high potential technological utility. 11,16,19,27,35,41,44,45 These NPOM designs mimic theoretical free-space dimer (FSD) designs, in which two metallic nanoparticles (NPs) are separated by a nanogap distance to create a hot spot. 36,44,45 The dielectric layer inserted between the NP and mirror acts as a virtual hot-spot region, in which attractive plasmonic properties can be realized.…”
Section: Introductionmentioning
confidence: 99%